A Rare Case Report of Ruptured Cyst Presenting With Acute Meningitis in an Untreated Neurocysticercosis - Shereef, Hammam (Cureus, 2021)
Neurocysticercosis (NCC) rarely presents as acute meningitis; however, when it does, it is not distinguishable clinically from other more common infectious etiologies. Here, we report a case of NCC presenting as acute meningitis, which also highlights the importance of brain MRI imaging rather than CT where possible, the need to include MRI of the spine in patients with the subarachnoid disease, and the limitations of NCC antigen detection assay in cerebrospinal fluid when used in ventriculoperitoneal shunt specimens. A prolonged course of albendazole, praziquantel, and corticosteroids led to the resolution of our patient's NCC.